PUSAT SUMBER BELAJAR PAI DALAM DUNIA PENDIDIKAN; SEBUAH KAJIAN KRITIS DAN PENGEMBANGANNYA - Asmuki, Asmuki; Hasanah, Hasanah (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2020)
The more practical mastery of information technology has an impact on the choice of varied learning resources. Current education requires students to access all the information needed to answer the problems they face and to improve their understanding of certain fields of science. Through the learning process, students can become empowered and creative people. The four pillars of learning, learning to know, learning to do, learning to be, learning to live together can be the basis of the process of empowering the lives of every student. In order to create creative learning activities, the learning resource center is present as a building designed in such a way as to store, care for, develop various learning resources for the benefit of teachers and students, especially in accessing learning resources regarding Islamic education. To develop a learning resource center, at least one must pay attention to teacher creativity, paradigms, facilities, and targets as well as time and management competencies.